INTRAOCULAR-PRESSURE VARIATIONS DURING EXTRACORPOREAL-CIRCULATION AND SOME INFLUENCING FACTORS - (:unkn) unknown (GEORG THIEME VERLAG, 1991)
Intraocular pressure (IOP) variations during extracorporeal circulation (ECC) and some influencing factors were studied prospectively in 38 patients undergoing cardiovascular surgery. IOPs were measured preoperatively, during EEC after 5 min, 10 min, and then every 15 min and on the first, second and third postoperative days. IOP, haematocrit, arterial perfusion pressure, partial O2 pressure, partial CO2 pressure, pH, and blood bicarbonate levels were measured simultaneously. After beginning ECC, arterial perfusion pressure and haematocrit values decreased suddenly while IOP was raised immediately. The sudden increase of blood volume at the start of ECC is the probable cause of IOP elevation. Afterwards IOP levels decreased to pre-ECC levels. We think that the drop is due to the effect of mannitol in the priming solution and hyposecretion of aqueous humor due to insufficient nutrition-oxygenation of the corpus ciliaris after the haemodynamics have stabilised.
Keywords: EXTRACORPOREAL CIRCULATION; INTRAOCULAR PRESSURE; HEMODILUTION; AQUEOUS HUMOR; ARTERIAL PERFUSION PRESSURE; CARDIOPULMONARY BYPASS; SURGERY